Các yếu tố ảnh hưởng đến sự hài lòng của người bệnh với chất lượng khám chữa bệnh tại các bệnh viện công ở TP Hồ Chí Minh - Nguyễn, Thị Ngọc Phương (2025)
The research identified the factors affecting patient satisfaction with the quality of medical examination and treatment of public hospitals in Ho Chi Minh city. Data was collected from 369 patients who used medical examination and treatment services in public hospitals through a pre-designed questionnaire using the convenient sampling method. Descriptive statistical methods, reliability testing through Cronbach’s Alpha, exploratory factor analysis (EFA), and multiple linear regression were used in this study. Research results showed that six factors affecting patient satisfaction with the quality of medical examination and treatment at public hospitals in Ho Chi Minh city are arranged in order from the highest to lowest as follows: (1) respect and caring, (2) facilities, (3) costs of medical examination and treatment, (4) medical examination and treatment procedures, (5) effectiveness of medical examination and treatment, and (6) other support services. As a result, the research raised some solutions to help improve patient satisfaction with medical examination and treatment of public hospitals in Ho Chi Minh city and provided more evidence to assist the Ministry of Health to enhance the Patient Experience Survey Toolkit more appropriately in the current context.